1993
DOI: 10.1016/0092-8674(93)90532-u
|View full text |Cite
|
Sign up to set email alerts
|

Inducibility and negative autoregulation of CREM: An alternative promoter directs the expression of ICER, an early response repressor

Abstract: cAMP-responsive element modulator (CREM) expression is tissue specific and developmentally regulated. Here we report that CREM is unique within the family of cAMP-responsive promoter element (CRE)-binding factors since it is inducible by activation of the cAMP signaling pathway. The kinetic of expression is characteristic of an early response gene. The induction is transient and cell specific, does not involve increased transcript stability, and does not require protein synthesis. Significantly, the subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
564
2
11

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 563 publications
(594 citation statements)
references
References 46 publications
17
564
2
11
Order By: Relevance
“…The products of the ICER transcripts is a group of proteins of approximately 13 ± 14 kD, which are generated from di erent splicing isoforms (Stehle et al, 1993;Molina et al, 1993). Western blot analyses with protein extracts prepared from control and NGF-treated PC12 cells were performed using an anti-ICER antibody.…”
Section: Induction Of Icer Expression Upon Ngf Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The products of the ICER transcripts is a group of proteins of approximately 13 ± 14 kD, which are generated from di erent splicing isoforms (Stehle et al, 1993;Molina et al, 1993). Western blot analyses with protein extracts prepared from control and NGF-treated PC12 cells were performed using an anti-ICER antibody.…”
Section: Induction Of Icer Expression Upon Ngf Treatmentmentioning
confidence: 99%
“…The P2 intronic promoter, which directs ICER transcription, contains a cluster of four CRE-like elements see Figure 3a). These sites are termed CAREs (for cAMP autoregulatory responsive elements; Molina et al, 1993) and were demonstrated to be responsible for cAMP inducibility and to be the targets of ICER negative autoregulation. PC12 cells were transfected with various reporter constructs containing di erent ICER promoter fragments.…”
Section: Induction Of Icer Expression Upon Ngf Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The CREM gene generates a family of activators and repressors by alternative splicing, translation initiation and use of an alternative intronic promoter (Delmas et al, 1992;Foulkes et al, 1992;Laoide et al, 1993;Molina et al, 1993). In order to determine the type of CREM transcripts which are induced in IPC-81 cells we used RNAse protection analysis (Figure 3a .…”
Section: Crem Induction In Ipc-81 Cells Upon Apoptosismentioning
confidence: 99%